SPE Annual Technical Conference and Exhibition 2001
DOI: 10.2118/71654-ms
|View full text |Cite
|
Sign up to set email alerts
|

Layered Modulus Effects on Fracture Propagation, Proppant Placement, and Fracture Modeling

Abstract: Hydraulic fracture geometry (i.e., critical results of length and proppant placement) is driven by four major in situ parameters: Fracture Height (H), Modulus (E), Fluid Loss (C), and "Apparent" Fracture Toughness (KI c-app ). In many (even most) cases, "Height" is the most important of these parameters – due to the need for some height confinement to achieve long fractures, or the need for height growth to insure good pay coverage. Due to this importance, industry research effort and most field measuring tech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
24
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(28 citation statements)
references
References 30 publications
4
24
0
Order By: Relevance
“…If the net pressure is not available for penetrating through high stress barrier layers, then fracture height must be contained. Studies have pointed out that modulus contrast can also have significant effect on fracture height growth (Smith et al, 2001;Gu and Siebrits, 2006). Lower modulus layers do not enhance, but hinder fracture height growth (Gu and Siebrits, 2006), which is also verified in the present paper.…”
Section: Introductionsupporting
confidence: 89%
See 2 more Smart Citations
“…If the net pressure is not available for penetrating through high stress barrier layers, then fracture height must be contained. Studies have pointed out that modulus contrast can also have significant effect on fracture height growth (Smith et al, 2001;Gu and Siebrits, 2006). Lower modulus layers do not enhance, but hinder fracture height growth (Gu and Siebrits, 2006), which is also verified in the present paper.…”
Section: Introductionsupporting
confidence: 89%
“…Fracture height has been recognized as one of the critical factors which can determine the success or failure of a hydraulic fracturing treatment. Many studies have been conducted for the effects of in-situ stresses, formation Young's modulus, fracture toughness and layer interfacial slip on hydraulic fracture height containment in layered formations (van Eekelen, 1982;Teufel and Clark, 1984;Thiercelin et al, 1987;Wang and Clifton, 1990;Warpinski et al, 1982Warpinski et al, , 1998Smith et al, 2001;Gu and Siebrits, 2006;Gu et al, 2008;Daneshy, 2009;Iyer and Podladchikov, 2009;Lewis et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…properties of caprocks and underlying rocks, are close to each other, there is an abrupt change in fracture height which is difficult to control. When fracture propagates from the reservoir with elastic modulus of 75 GPa to the caprocks and underlying rocks with elastic modulus of 80 GPa, the fracture width shrinks at both the top and bottom parts which is identical with the result of Smith et al (Smith et al, 2001) obtained from planar 3D model. The reservoir with low elastic modulus restricts the fracture height growth; however, the control mechanism differs from that in the reservoir of high elastic modulus.…”
Section: The Influence Of Elastic Modulus On the Hydraulic Fracture Gsupporting
confidence: 84%
“…Teufel and Clark [81] found that the elastic properties of either side of the interface could influence the propagation of vertical growth by affecting the vertical distribution of the minimum horizontal stress state, because the increase in minimum horizontal in-situ stress in the bounding layers and a weak interfacial shear strength of the layers could contain vertical growth of hydraulic fractures. For composite rock, differences in Young's Moduli and the fluid volume within the fracture and the conductivity and productivity in adjacent layers can influence the width of hydraulic fracture if it grows across the interfaces [28,79]. The first is layers of higher strength may be micro-cracked for they take more stress; yielding in soft rock that dissipates the energy can also contain the fracture or cause discontinuous fractures; interface slip may retain the hydraulic fracture or deviate the path, as shown in [86] (Fig.…”
Section: Influences Of Complex Geological Structures On Hydraulic Framentioning
confidence: 99%